DECISION SUPPORT SYSTEM FOR DETERMINING THE LOCATION OF SEMINAR - Muttaqin Muttaqin (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2018)
The appropriateness of a location to be selected as a seminar location is affected by many supporting factors, so that the location is suitable as a single choice. Hence, there should be made a process to decide a location whether it is proper or not to match some assessment criteria conceived before. There are 8 assessment criteria with 22 sub-criteria each. The result of the assessment forms as a total values which has limited values, determined by equal intensity (degree of assessment), which are low, medium, and high. Once the assessment process is done, then the next step is verifying comparison between one criteria with others, as well as comparison between one sub-criteria and other sub-criteria to acquire alternative ranking value. Decision-making support system which is developed in this study uses Analytical Hierarchy Process (AHP). AHP is used as a decision-making process tool by the decision maker to exercise a decision which faces several problems from a range of criteria. While Geographical Information System (GIS) is used to handle geography-reference data, which are input, output, data management (data storage and retrieval), and analysis and data manipulation which resulted on a map. The combination of both processes would create a new system which its mathematic calculation uses AHP but the result is outputted on an interactive map, generated by the GIS. Keywords: AHP, GIS, Decision maker, seminar location